Evaluation of in vitro antidiabetic activity of selected flavonoids: structure activity relationship based study - Ahmed, Qamar Uddin (2018)
Flavonoids have been reported to exert antihyperglycemic effect and have potential to enhance the current therapy options against type 2 diabetes mellitus. However, the structure activity relationships (SAR) studies of flavonoids against this disease have not been thoroughly understood. In the present study, fourteen structurally related flavonoids were taken into account for in vitro antidiabetic evaluation. Cell viability of RIN-5F pancreatic cells and 3T3-L1 pre-adipocyte cells were initially tested, then, insulin secretion assay of RIN-5F as well as adipogenesis, and glucose uptake measurement of adipocyte were investigated. Subsequently, protein expression study through adipokines measurement, western blotting analysis against GLUT4 and C/EBP-α was carried out. The results from insulin secretion, adipogenesis, glucose uptake and protein expression assays revealed that the methoxy group at position C-8 is responsible for antidiabetic property of selected flavonoids via glucose uptake mechanism indicated by up regulation of GLUT4 and C/EBP-α expressions. The mechanism was seen to be enhanced by the addition of acetate group at C-5 and C-7. Further investigation is still necessary to clarify biological outcomes and activities of flavonoids, to distinguish their metabolites with special functional groups, thus meeting therapeutic and nutritional requirements.